Pengembangan Kuesioner Pengetahuan Masyarakat tentang Penyakit Ginjal Kronik - Irwan Nuryana Kurniawan; Mursidha Rakhmi Salicha; Rahma Yuantari; Vitarani Dwi Ananda Ningrum (Fakultas Farmasi Universitas Setia Budi, 2022)
To reduce the prevalence of chronic kidney disease, a pillar of health paradigms through community empowerment has been introduced. Society with profound knowledge of such disease has proved to be able to raise awareness of kidney disease early detection. Meanwhile, limited data on public knowledge of chronic kidney disease make the education programs in health promotion seem ineffective. This study therefore aims to develop a questionnaire with high validity and reliability to assess public knowledge of this disease. The development included five stages of conceptualisation, instrument construction, a trial with Study 1 of 240 medical and non-medical students and Study 2 of 300 participants from Sleman Regency in Yogyakarta, a test of the revision, and an analysis using the Cronbach’s alpha reliability test. A validity test compared this questionnaire with another reliable questionnaire. Both studies yielded a knowledge scale with two variables comprising kidney disease knowledge (risk factors, causes, symptoms, management) and kidney disease prevention knowledge with Cronbach’s alpha of 0.623 and 0.703 (Study 1) and 0.361 and 0.545 (Study 2). This has proved that the preliminary psychometric evidence (factor structure, reliability, convergent validity) satisfied the requirements for an instrument used to measure public knowledge of chronic kidney disease.